A novel D–π–A small molecule with N-heteroacene as acceptor moiety for photovoltaic application. (November 2015) - Wang, Chengyuan; Okabe, Takuya; Long, Guankui; Kuzuhara, Daiki; Zhao, Yang; Aratani, Naoki; Yamada, Hiroko; Zhang, Qichun
Abstract: Organic π -conjugated small molecules have attracted much attention for developing high performance organic photovoltaics (OPVs) due to their well-defined molecular structure, easily controlled energy levels and absorption, and more accurate simulation-experiment match. A novel small molecule combing a N -heteroacene (acceptor moiety) and benzo[1, 2- b :4, 5- b ′]dithiophene (donor unit) together through a π -conjugated bridge (3, 3″-dioctyl-2, 2′:5′, 2″-terthiophene), has been synthesized and characterized. The blended films of this small molecule with different acceptors have a wide absorption in visible region, which makes it possible for application in OPVs. The as-fabricated devices with PEDOT:PSS as an anode buffer layer show the power conversion efficiency at around 1%. By replacing PEDOT:PSS with MoO3, the power conversion efficiency is almost doubled up to 1.97%. AFM images and XRD patterns are employed to investigate the morphologies of the active layer. Consistent with the J – V curves and EQE spectra, the higher power conversion efficiency probably comes from the good alignment of the HOMO energy level of the small molecule with the work function of anode buffer layer and reduced chemical interactions between active layer and anode buffer layer. Highlights: A novel D– π –A small molecule has been synthesized and characterized. The standard BHJ-structured OPV device using this small molecule as the donor has been fabricated. The efficiency of the as-fabricated devices can be as high as 1.97%.